A non-parametric structural hybrid modeling approach for electricity prices. Issue 2 (1st February 2016) - Moazeni, S.; Coulon, M.; Rueda, I. Arciniegas; Song, B.; Powell, W.B.
Abstract : We develop a stochastic model of zonal/regional electricity prices, designed to reflect information in fuel forward curves and aggregated capacity and load, as well as zonal or regional price spreads. We use a non-parametric model of the supply stack that captures heat rates and fuel prices for all generators in the market operator territory, combined with an adjustment term to approximate congestion and other zone-specific behaviour. The approach requires minimal calibration effort, is readily adaptable to changing market conditions and regulations, and retains sufficient tractability for the purpose of forward price calibration. The model is illustrated for the spot and forward electricity prices of the PS zone in the PJM market, and the set of time-dependent risk premiums are inferred and analysed.